QUANTUM DYNAMICS OF THE He + Li2 INELASTIC SCATTERING - Akpinar, Sinan; Turmus, Tunay; Surucu, Seda (World Scientific Publ Co Pte Ltd, 2011)
In this paper, we report the results of three dimensional time dependent quantum wave packet calculations carried out for He+Li-2 inelastic reaction in the collision energy range 0.43 1.18 eV. A three dimensional potential energy surface (PES) computed by Varandas was used for the dynamical calculations.(1) The state to state and state to all transition probabilities for total angular momentum J = 0 have been calculated in a broad range of collision energies. Integral cross-sections and rate constants have been calculated from the wave packet transition probabilities by means of J-shifting approximation based on a capture model and a uniform J-shifting method for J > 0.
Keywords: Inelastic scattering; quantum wave packet; reaction rate constants